Survival and toxicity following sequential multimodality treatment including whole abdominopelvic radiotherapy for patients with desmoplastic small round cell tumor. Issue 1 (April 2016) - Osborne, Eleanor Marshall; Briere, Tina Marie; Hayes-Jordan, Andrea; Levy, Lawrence B.; Huh, Winston W.; Mahajan, Anita; Anderson, Peter; McAleer, Mary Frances
Abstract: Background and purpose: Desmoplastic small round cell tumor (DSRCT) is a rare, aggressive malignancy. We report survival rates and toxicity associated with sequential multimodality treatment including whole abdominopelvic radiation therapy (WART). Material and methods: Medical records of 32 patients with DSRCT treated at our institution were reviewed. Patients underwent chemotherapy, cytoreductive surgery with hyperthermic intraperitoneal chemoperfusion (HIPEC), followed by WART with intensity-modulated radiation or volumetric-modulated arc therapy. Results: Median overall survival (OS) was 60 months. After 18 months of follow-up, 20 patients (62.5%) had disease recurrence and median disease-free survival (DFS) was 10 months. Median time to extrahepatic abdominal failure was 19.4 months. Factors affecting time to local progression included liver metastases at diagnosis, and an interval of greater than 5.6 months between diagnosis and HIPEC or greater than 2.1 months between HIPEC and WART. None of these factors altered OS. Grade 3 or higher toxicities occurred in 84% of patients. Conclusions: WART following chemotherapy, surgical cytoreduction and HIPEC is an aggressive treatment for DSRCT patients and can result in severe side effects. Our median OS of 5 years is favorable compared to prior studies, despite a median DFS of only 10 months, which may be due to improved salvage therapies.